Asymptotic Stability of Caputo Fractional Singular Differential Systems with Multiple Delays - Priyadharsini, Sivaraj; Govindaraj, Venkatesan (Discontinuity, Nonlinearity, and Complexity, 2026)
In this work, Lyapunov functions combining Matrix inequalities or Matrix equations are developed to analyze the asymptotic stability of Caputo fractional singular systems with multiple time-varying delay. Integer-order derivatives of the Lyapunov functions are used to derive asymptotic stability criteria. The main advantage of applying stability criteria is that no need of solving roots of transcendental equations. Some examples are provided to explain the effectiveness of the proposed criteria.